(untitled) (Community Based Medical Journal, 2015)
Intracapsular femoral neck fracture is a common injury in elderly person. The primary goal of treatment is to return the patient to him or her pre-fracture functional status. The surgical treatment is the treatment of choice, lip replacement arthroplasty (hemi or total) is a viable treatment option. Thirty elderly patients (age 50-80 years) with a displaced intracapsular femoral neck fracture were under treatment over a five year period (January 2010 to December 2015). All of them underwent hemiarthroplasty either unipolar or bipolar, after appropriate medical and anesthetic fitness. The patients were reevaluated at six weeks, at six months postoperative interval and assessed using Harris hip score (HHS) and visual analogue scale (vas) for evaluation of outcome. The mean age of patients was 64.5 years and male female ratio was 43.3% - 56.7%. The mean HHS score was 85.3 by the end of the 6 months. The mean score on VAS scale was 60mm (moderate) at 2 weeks, 40mm (mild) at six weeks and 4mm (mu) at 6 months follow up visit. No significant complications were observed except hip pain. No patients needed revision surgery. Herniarthroplasty is the treatment of choice in elderly population with displaced femoral neck fracture (Garden type III or IV); provides early ambulation, good functional outcome, pain free joint with minimal complications without the need for revision surgery. CBMJ 2015 July: Vol. 04 No. 02 P: 8-12